Biliary drainage surgery before or after 3 months of life versus primary liver transplantation in children with biliary atresia: comparative cohort study. Issue 2 (23rd March 2023) - Fuchs, Juri; Mrad, Chaima; Gonzales, Emmanuel; Ndiaye, Dior; Fouquet, Virginie; Héry, Géraldine; Baujard, Catherine; Guérin, Florent; Branchereau, Sophie
Abstract: Background: Early biliary drainage surgery (BDS; Kasai) is associated with longer transplant-free survival in biliary atresia. However, evidence is lacking on whether an age limit can be established at which liver transplantation should be performed as first-line treatment for children with a delayed diagnosis of biliary atresia. The aim of the current study was to compare the outcome of a large cohort of children with biliary atresia who underwent BDS after 90 days of life with those who underwent early BDS (before 90 days) and those who did not receive BDS and were directly referred for primary liver transplantation. Methods: All patients with biliary atresia treated at Bicêtre, Paris-Saclay University Hospital between 1995 and 2017 were analysed in this STROBE-compliant study. Three groups were defined: BDS before 90 days of life (early BDS); BDS after 90 days of life (late BDS); and patients without BDS who were referred for primary liver transplantation (no BDS). Patient characteristics, overall survival, and native liver survival were compared. Results: Of 424 children with biliary atresia, 69 patients (16 per cent) were older than 90 days when they underwent BDS. Twenty-five patients had no BDS and were referred for primary liver transplantation (6 per cent). The main reason for not performing BDS was manifest portal hypertension (18/25). Two- and 5-year transplant-free survival were significantly higher in patients with late BDS compared with no BDS (53.5 versus 12.0 per cent respectively for 2-year data and 30.4 versus 4.0 per cent respectively for 5-year data, P < 0.001). Five- and 10-year overall survival did not differ between early BDS (92 and 91 per cent respectively), late BDS (88 and 83 per cent respectively) and no BDS (80 and 80 per cent respectively, P = 0.061). Conclusion: Age alone should not routinely be considered a contraindication to BDS in patients older than 90 days. Liver transplantation in infancy (less than 12 months) could be avoided in 88 per cent of cases with late diagnosis of biliary atresia and is delayed significantly even when BDS is performed after 3 months. Overall survival is at least equal to patients who are referred for primary liver transplantation. Abstract : Evidence is lacking on whether an age limit can be established at which liver transplantation (LT) should be performed as first-line treatment for children with a delayed diagnosis of biliary atresia (BA). Our study results show that LT in infancy (less than 12 months) can be avoided in 88 per cent of cases with late diagnosis of BA and is delayed significantly even when Kasai is performed after 3 months. Late Kasai can be recommended even in cases of late diagnosis of BA.